2022
DOI: 10.1200/jco.21.02986
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response to COVID-19 mRNA Vaccine in Patients With Lung Cancer After Primary Immunization and Booster: Reactivity to the SARS-CoV-2 WT Virus and Omicron Variant

Abstract: PURPOSE To examine COVID-19 mRNA vaccine–induced binding and neutralizing antibody responses in patients with non–small-cell lung cancer (NSCLC) to SARS-CoV-2 614D (wild type [WT]) strain and variants of concern after the primary 2-dose and booster vaccination. METHODS Eighty-two patients with NSCLC and 53 healthy volunteers who received SARS-CoV-2 mRNA vaccines were included in the study. Blood was collected longitudinally, and SARS-CoV-2–specific binding and neutralizing antibody responses were evaluated by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 29 publications
(48 reference statements)
2
27
0
Order By: Relevance
“…Studies conducted in populations defined by particular diseases or treatment (such as autoimmune conditions treated with immunosuppressive agents, myeloma, lung cancer and dialysis) have provided mixed results relating to the impact of ethnicity on immunogenicity of SARS-CoV-2 vaccine. 16 , 17 , 18 , 19 , 20 , 21 A recent study reporting findings from a large cohort of UK healthcare workers (HCWs) found higher SARS-CoV-2 anti-spike titres in ethnic minority vaccinees than in their White counterparts, 22 which contrasts with another UK HCW study which found lower peak anti-spike antibody titres in Black HCWs compared to White HCWs and did not find differences between the White and Asian groups. 23 A large UK observational study in the general population found South Asians vaccinees to have higher combined IgG, A and M titres against SARS-CoV-2 than those from White groups.…”
Section: Introductionmentioning
confidence: 94%
“…Studies conducted in populations defined by particular diseases or treatment (such as autoimmune conditions treated with immunosuppressive agents, myeloma, lung cancer and dialysis) have provided mixed results relating to the impact of ethnicity on immunogenicity of SARS-CoV-2 vaccine. 16 , 17 , 18 , 19 , 20 , 21 A recent study reporting findings from a large cohort of UK healthcare workers (HCWs) found higher SARS-CoV-2 anti-spike titres in ethnic minority vaccinees than in their White counterparts, 22 which contrasts with another UK HCW study which found lower peak anti-spike antibody titres in Black HCWs compared to White HCWs and did not find differences between the White and Asian groups. 23 A large UK observational study in the general population found South Asians vaccinees to have higher combined IgG, A and M titres against SARS-CoV-2 than those from White groups.…”
Section: Introductionmentioning
confidence: 94%
“…Articles that focused only on LC patients showed that COVID-19 mRNA and viral vectorbased vaccines can safely generate humoral immune responses in these patients, albeit at somewhat diminished levels compared to those in the general population. Out of the nine articles that specifically examine vaccine immunogenicity in LC patients, six demonstrate significant differences in median titers following the primary vaccination series when compared to HC data [29][30][31][33][34][35]. The variety of emerging and still-evolving Omicron variants of SARS-CoV-2, with the ability to overcome primary vaccination-induced immunity, present significant new threats to LC patients.…”
Section: Discussionmentioning
confidence: 99%
“…IgG titers were maintained over time with low infection and reinfection rates with a mild clinical course. None of the reports by Valanparambil et al [33], Mack et al [32], and Hernandez et al [28] observed differences in serologic responses as a result of cancer treatment in LC patients, but with significant heterogeneity in treatment modalities, were not necessarily powered to do so.…”
Section: Sars-cov-2 Vaccines Immunogenicity In Patients With Lc or Th...mentioning
confidence: 95%
See 1 more Smart Citation
“…In the article accompanying this editorial, Valanparambil et al 6 performed longitudinal studies of anti–severe acute respiratory syndrome coronavirus 2 SPIKE protein titers and the ability of these antibodies to neutralize authentic virus in patients with lung cancer after vaccination and boost with a mRNA vaccine and although 75% of patients mounted a good anti-viral immune response, 25% failed to generate an adequate immune response after initial vaccination, raising questions about causes of this failure and optimal approaches to vaccinate patients with lung cancer. This study indicates both the need to monitor our patients with lung cancer for response to COVID-19 mRNA vaccines, identify the nonresponders for follow-up and further attempts at immunization, and continue collecting and analyzing clinicodemographic information and biospecimens from our patients.…”
mentioning
confidence: 95%